Developing the World's Brightest WUXGA OLED Microdisplay. (23rd March 2022) - Ghosh, Amal; Khayrullin, Ilyas; Vazan, Fridrich; Zhao, Fangchao; Lin, Howard; Prache, Olivier; Sziklas, Laurie; Peruvemba, Sri; Sculley, Andrew
Abstract: With the advent of AR/VR technologies, microdisplay performance requirements are more demanding. Although OLED microdisplays are well suited to satisfy most of these stringent requirements, luminance still needs to be improved.